Rationalization of Modern Life: The Case of Water Consumption in Moscow - Andreeva, Anastasia; Klimeshova, Julia; Kudryavtseva, Maria; Lobanova, Anastasia (Journal of Economic Sociology, 2017)
In a risk society, healthism, medicalization, and the expansion of the market for bottled water all contribute to the disciplinary self-management of drinking water consumption. Such changes align with the predictions of classical sociologists like Weber and Simmel that the phenomenon of rationalization would extend to all spheres of society, including everyday life. Based on qualitative research data on drinking water consumption in Moscow, this study assesses how such trends are manifested in contemporary Russian society. The study demonstrates an increasing emphasis on managing thirst. In certain social contexts (including sports, weight loss, and pregnancy), the habitualization of socially constructed norms of water consumption has transformed these into an internal need. The mechanisms of control and calculative behavior are manifested in both the conscious attempts and unconscious measuring tactics developed by Muscovites to increase the volume of water being drunk . Ordinary people who are anxious about the safety of drinking water seek institutional support from the state, advertisements for bottled water, and expert knowledge of various kinds. Because the quality of drinking water is perceived to be an existential issue, the lack of certainty around this issue sometimes gives rise to irrational beliefs. The researchers were especially surprised to find references to “life-giving” or “dead” water in the narratives of respondents with a university education, including some with medical degrees.